Respuesta :

CPED

Answer:

(i)   x = 1/2

(ii)  x^-2 = (2/3)^12

Step-by-step explanation:

Part 1

Preceding from given question:

As bases are same so powers will be added as follows:

(2/3)^2x+1 + x = (3/2)^-2-x

Or

(2/3)^3x+1  = (3/2)^-(2+x)

By inverting right fraction

(2/3)^3x+1 = (2/3)^2+x

Now both bases are same so cancel out them

3x + 1 = 2 + x

3x - x = 2 - 1

2x = 1

x = 1/2

-------------------------------------------------------------------------

Part 2

Preceding from given question:

The fraction on right will be inverted and sign will be changed

x = (3/2)^2 * (3/2)^4

Bases are same so powers will be added

x =  (3/2)^6 = 729/ 64 ---------- eq1

We have to find x^-2 so

x^-2 = (729/64)^-2

by inverting to change negative sign

x^-2 = (64/729)^2

OR

Using eq1:

x^-2 = (2/3)^12

i hope it will help you!

ACCESS MORE